2010
DOI: 10.1080/09500341003774704
|View full text |Cite
|
Sign up to set email alerts
|

Complex spatial structures due to atomic coherence

Abstract: The coupling of diffraction and optical coherence of a three-level medium in an optical cavity is considered. Self-organisation and pattern formation due to a combination of electromagnetically induced transparency, close-to-resonance Kerr effects and diffraction is demonstrated. Self-focusing in the peaks of the resulting Turing pattern leads to localised amplification of the input pump. Spatial dissipative solitons with controllable position, dispersion and coherence are also described

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Details of these structures and the transition to squares via magnetic field and intensity are currently under investigation. Some theoretical papers considered the possibility of coherence based self-organized states in cavities [133,134], but we are not aware of any previous experiment before Ref. [51] demonstrating self-organized coherences.…”
Section: Quadrupole Structuresmentioning
confidence: 98%
“…Details of these structures and the transition to squares via magnetic field and intensity are currently under investigation. Some theoretical papers considered the possibility of coherence based self-organized states in cavities [133,134], but we are not aware of any previous experiment before Ref. [51] demonstrating self-organized coherences.…”
Section: Quadrupole Structuresmentioning
confidence: 98%
“…Equation (1) is a generalization of the model introduced in Ref. [10] since in the evaluation of ρ 13 we used a less stringent condition of | | 2 |E 2 | 2 instead of | | |E 2 | 2 . The bistable nature of the light-atom interaction and the capability of the system for displaying EIT in the present model (1) are extended to a wider parameter space than that of [10] [see, for example, Figs.…”
Section: The Modelmentioning
confidence: 99%
“…The complex spatial structures forming in nonlinear cavities displaying electromagnetically induced transparency (EIT) [10] show generalized multistability of the kind described above. In particular, it will be shown that different spatially periodic structures (optical patterns) are obtained for different initial conditions but the same parameter values.…”
Section: Introductionmentioning
confidence: 98%
“…All fields E, E I and E 2 are normalized to the square root of the saturation intensity of the first atomic transition. θ is the detuning between the cavity resonance and the frequency of the injected pump beam normalized to the inverse of the photon lifetime, and ρ 13 is the off-diagonal density matrix element proportional to the field amplitude E and the complex susceptibility χ via the relation [36,37]:…”
Section: The Modelmentioning
confidence: 99%